Kajian Scientometrics: Analisis Jaringan Sosial pada Publikasi Internasional Indonesia Bidang Kimia - Irene Muflikh Nadhiroh; Muhammad Nur Aidi; Bagus Sartono (Center for Science and Technology Development Studies, Indonesian Institute of Sciences, 2015)
The importance of the use of more precise methods in the management of R & D budget to encourage the development of a variety of methods based on the data in the R&D policymaking process. Scientometrics is one area of science that can be used in the management of R&D efforts in a more effective and efficient ways. Asociated with limited budgets and goals that must be achieved in the development of science and technology, the budget must be allocated to give a great impact on the development of Indonesia. Data of Indonesian international publications in Chemistry area of science was used in this study to assess the social network among authors of scientific paper in Indonesia. The objectives of this study are to provide a new method of the R&D budgd alocation process better in the future and provide policy recommendations related to the condition of social networks that has been studied. Networks among Indonesian authors in the internasional publication, especially in Chemistry area are still very fragmented, very few relationships that are formed between the authors. In addition the synergy between academia-industry-government is still less visible. Relationships between authors from different institutions are also still very little, the majority of authors writing with institution’s colleagues.Therefore, this study provides some policy recommendations, namely: i) providing wide space for academicians in Indonesia, both in university and in government R & D institutions and NGOs to collaborate; ii) the government is expected to be more proactive in communicating with the relevant academic research needs requiring for the livelihood of the people in the future; iii) the existence of incentives and rewards for the academia and the private sector to collaborate and produce a useful research; iv) the government provide greater opportunities for researchers in the private sector to collaborate with academician at universities and R&D institutions, both in the implementation of research, research funding, research infrastructure and the use of other research activities.